New Reassortant H5N6 Highly Pathogenic Avian Influenza Viruses in Southern China, 2014 - Jiao, Peirong; Cui, Jin; Song, Yafen; Song, Hui; Zhao, Zhishan; Wu, Siyu; Qu, Nannan; Wang, Nianchen; Ouyang, Guowen; Liao, Ming (Frontiers in Microbiology, 2016)
New reassortant H5N6 highly pathogenic avian influenza viruses were isolated from apparently healthy domestic ducks in Southern China in 2014. Our results show that the viruses grew efficiently in eggs and replicated systemically in chickens. They were completely lethal in chicken (100% mortality), and the mean death time (MDT) was 6 to 7 days post-inoculation (DPI). The viruses could transmit in chickens by naïve contact. BLAST analysis revealed that their HA gene was most closely related to A/wild duck/Shangdong/628/2011 (H5N1), and their NA genes were most closely related to A/swine/Guangdong/K6/2010 (H6N6). The other genes had the highest identity with A/wild duck/Fujian/1/2011(H5N1). The results of phylogenetic analysis showed that their HA genes clustered into clade 2.3.4.4 of the H5N1 viruses and all genes derived from H5 were Mix-like or H6-like viruses. Thus, the new H5N6 viruses were reassortanted of H5N1 and H6N6 virus. Therefore, the circulation of the new H5N6 avian influenza viruses may become a threat to poultry and human health.